Roots of religious radicalism in Central Asia - Sengirbay, M. (ҚазҰУ хабаршысы. Философия, саясаттану және Мәдениеттану, 2018)
The radicalism in Central Asia has both domestic and external characteristics. This article analyzes all the factors that led the radicalism to flourish in the region after the collapse of the Soviet Union. The main conclusion of this article is that the phenomenon of radicalization in Central Asia is a combination of classical social movement theory elements and other political, geopolitical, historical, societal factors that are unique only in this region and in this period of history. Key words: Central Asia, radicalization, religious radicalism, Islam, terrorism, Hizb-ut-tahrir.